“EVERY GENERATION HAS ITS SHERLOCK”: THE CHARACTER’S IMAGE IN THE FILM ADAPTATIONS OF STORIES BY A. CONAN DOYLE ABOUT SHERLOCK HOLMES / «КАЖДОМУ ПОКОЛЕНИЮ — СВОЙ ШЕРЛОК»: ОБРАЗ ГЕРОЯ В ЭКРАНИЗАЦИЯХ ПРОИЗВЕДЕНИЙ А. КОНАН ДОЙЛА О ШЕРЛОКЕ ХОЛМСЕ - BULGAROVA BELLA A. / БУЛГАРОВА Б.А.; OVCHARENKO ALEXEY YU. / ОВЧАРЕНКО А.Ю.; BARABASH VICTOR V. / БАРАБАШ В.В.; VOROPAEVA JULIA А. / ВОРОПАЕВА Ю.А. (Наука телевидения, 2021)
The article covers the problem of the protagonist’s image portrayal in modern cinema on the example of the three most recent film adaptations based on works by Conan Doyle. The relevance of this scientific issue is explained by the fact that the peculiarities of representing the character in modern cinema partly reflect the state of society itself, its social problems, phobias and neuroses. Cinematography, like no other type of contemporary art, has broad opportunities to embody almost any character in three-dimensional reality, which imposes a certain social responsibility for the results of the main characters’ portrayal. The appeal to the archetypal images of world literature implies not only the openness of improvisation, but also the preservation of the character’s social function. The article analyzes the representation of one of such archetypal images of world significance—Sherlock Holmes. The research methodology is based on a systematic approach and general scientific methods, and also includes special methods: content analysis of scientific literature related to the topic; the method of sociological survey (questionnaire survey), the method of statistical analysis. The empirical study, the results of which are presented in this article, is based on three screen adaptations of the Sherlock Holmes stories, produced in the 2000s in Great Britain, Russia and the United States. The study involved 150 respondents, whose answers were converted from a qualitative to a quantitative format to analyze the specifics of the representation of the main character (the protagonist). The authors of the article came to the following conclusions: in modern film adaptations the protagonist is portrayed not as a genius of the scientific method of thinking, but as a sociopath who is unable to interact with society without an intermediary (a companion character). Moreover, modern screen adaptations violate the archetypal image itself due to improvisations with the static characteristics of the character, which leads to a negative perception of such a character by the audience. The very strengthening of sociopathic features of the protagonist’s character, shifting the emphasis from the idea of higher justice, from eternal values to private motives, lead to a certain simplification of the character, and also serve as an indicator of the state of society itself. The theoretical significance of the research is determined by the fact that this article offers original criteria developed by the authors to analyze the representation of the character. The practical significance of the article is backed by the conclusions and results of the study, which can be used for further work to identify the impact of characters’ representations on shaping value orientations in modern society.